2009
DOI: 10.1123/apaq.26.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Eurofit Special: European Fitness Battery Score Variation among Individuals with Intellectual Disabilities

Abstract: The Eurofit Special Test is a battery of motor fitness tests resulting from a 10-year project of the Committee of Experts for Sports Research and is comprised of strength, speed, flexibility, and balance. The purpose of this study was to investigate whether the Eurofit Special was able to distinguish variations in functioning among individuals with intellectual disabilities. Significant differences were found in long jump flexibility 25-m dash, medicine ball throw, balance walk, sit ups in 30-s. Analyses demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 11 publications
2
61
0
7
Order By: Relevance
“…Possibly the non existence of JG could be explained on the peculiarities related with people with MI during jumping. Generally speaking people with MI present a deficit in all types of jumping (Skowronski et al 2009, Hasani et al 2013 The only relevant study which examined a similar case giving thus an indirect support to the current study is the one by Hassani et al (2014), were the vertical countermovement jump examined in young adolescent MR. Our assumption is based on the fact that both DJ and counter movement jump are classified into the group of SSC jumps, where muscle activation, storage and recoil of elastic energy and stiffness regulation occur (Kurokawa, Fukunaga, Nagano, & Fukashiro, 2003). In the Hassani et al (2014) study, it was observed that junior MI presented lower countermovement jump height, while they developed lower muscle activation, power and stiffness.…”
Section: Jpes ®mentioning
confidence: 71%
See 1 more Smart Citation
“…Possibly the non existence of JG could be explained on the peculiarities related with people with MI during jumping. Generally speaking people with MI present a deficit in all types of jumping (Skowronski et al 2009, Hasani et al 2013 The only relevant study which examined a similar case giving thus an indirect support to the current study is the one by Hassani et al (2014), were the vertical countermovement jump examined in young adolescent MR. Our assumption is based on the fact that both DJ and counter movement jump are classified into the group of SSC jumps, where muscle activation, storage and recoil of elastic energy and stiffness regulation occur (Kurokawa, Fukunaga, Nagano, & Fukashiro, 2003). In the Hassani et al (2014) study, it was observed that junior MI presented lower countermovement jump height, while they developed lower muscle activation, power and stiffness.…”
Section: Jpes ®mentioning
confidence: 71%
“…Generally speaking, MI have a deficit compared to typical population for fitness parameters such as strength and motor skill (LeClair, Pollock, & Elliott, 1993;Vuijk, Hartman, Scherder, & Visscher, 2010).This has been attributed to a failure of central drive (Haier, Jungb, Yeoc, Heada, & Alkired, 2004;Yu, Li, Liu, Qin, Li, Shu, N., et al 2008) and to environmental parameters such as inactivity (Horvat & Franklin, 2001). The majority of studies regarding jumping performance are related with horizontal jumping (Skowronski, Horvat, Nocera, Roswal, & Croce, 2009). Nevertheless, few studies have addressed vertical jumping in MI (Hassani, Kotzamanidou, Fotiadou, Patikas, Evagelinou, & Sakadami, 2013;Hassani, Kotzamanidou, Tsimaras, Lazaridis, Kotzamanidis, & Patikas, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Нижа постигнућа у моторичким способностима код особа с интелектуалним сметњама огледају се и у брзини и координацији покрета (Bala i sar., 1984;Nikolić i Ilić, 2007). На стандардним фитнес тестовима кoјима се процењује снага, издржљивост, флексибилност, моторна координација, ова деца постижу знатно ниже резултате (Chaiwanichsiri et al, 2000;Guideti et al, 2010;Skowronski et al, 2009). Лошија постигнућа у области моторичких способности повезана су са сниженим нивоом интелектуалног функционисања, тешкоћама у учењу процедура за извођење како моторних тако и менталних акција, усмеравању пажње, радној меморији и компонентама контроле покрета (Bala i sar., 1984).…”
Section: моторичке способности ученика са сметњама у развојуunclassified
“…were taken to calculate their body mass index (BMI). Physical fitness was assessed with Eurofit Special test (Skowronski et al, 2009), and additional balance tests at the beginning and at the end of the experiment after 10 months.…”
Section: Methodsmentioning
confidence: 99%